First Mover Strategy Analysis on Volvo Buses India Pvt Ltd. - ABDUL RASHEED, HARA TWO (2012)
This paper includes the research on first mover strategy and its experience advantages, considering the company Volvo Buses India. The company and its operations are studied directly and indirectly to connect the findings with theories. Proven theories by research scholars and industry experts are used to analyse the effects and advantages of the strategy and conclusions are drawn out to give recommendation for the company as a research paper finding.